Measures of Financial Constraints in Kenya - Kirui, Benard Kipyegon; Wawire, Nelson H.W. (International Journal of Economics and Financial Issues, 2018)
Understanding the effect of financial constraints on firms' real decisions requires accurate identification of financially constrained firms. Unfortunately, identifying financially constrained firms is a challenge that is yet to be resolved. Against this background, this study identified financially constrained firm-years in Kenya and evaluated how well proxies of financial constraints generated in an endogenous switching regression context measure financial constraints. About 66 percent of the firm-years in the sample considered are suffering from financial constraints. This suggests that financial constraint problem is affecting a higher number of firms over a longer period of time. Furthermore, there is no efficiency gain in using endogenous switching regression indices since the sample separation produced by the initial values outperformed endogenous switching regression final classification values. In particular, size-age measure does a better job of identifying financially constrained firms and producing consistent results, and is the only measure that approximates experienced financial constraints well. Keywords: Manufacturing, investment, capital structure JEL Classifications: D82, D92, E22, G31, G32, G33, L60